The Digital Heritage of Covid-19 's Governance: How to Upgrade and Use the "Health Code" in the Post-Epidemic Era - Wu Siqi; Wu Yi (Jurnal Audiens, 2021)
The outbreak of Covid-19 accelerated the practice of digital survival, and the "health code" launched based on the needs of epidemic prevention and control has become the representative of digital survival media, which is jointly built by science and technology enterprises and government departments. it has realized the full-state use in China, and accumulated long-term digital survival experience for the country, enterprises and individuals. At the same time, there are some media ethical problems in the use of Health Code, such as distinguishing users, leaking information, imprisoning the body and leading to the lack of subjects. In order to resolve the risk, we should re-examine the relationship between people and the media from the perspective of the subject, treat "health code" as a digital projection of personal health, and regain the service principle of digital technology. Humanize the "health code" and other digital media.